Ventilator-Associated Tracheobronchitis: To Treat or Not to Treat? - Despoina Koulenti; Kostoula Arvaniti; Mathew Judd; Natasha Lalos; Iona Tjoeng; Elena Xu; Apostolos Armaganidis; Jeffrey Lipman (Antibiotics, 2020)
Ventilator-associated tracheobronchitis (VAT) is an infection commonly affecting mechanically ventilated intubated patients. Several studies suggest that VAT is associated with increased duration of mechanical ventilation (MV) and length of intensive care unit (ICU) stay, and a presumptive increase in healthcare costs. Uncertainties remain, however, regarding the cost/benefit balance of VAT treatment. The aim of this narrative review is to discuss the two fundamental and inter-related dilemmas regarding VAT, i.e., (i) how to diagnose VAT? and (ii) should we treat VAT? If yes, should we treat all cases or only selected ones? How should we treat in terms of antibiotic choice, route, treatment duration?